Effect of hepatogomax on serum alkaline phosphatase, bilirubin, gamma-glutamyl transferase levels in Sprague Dawley rats cirrhosis - Elfrida Sianturi; Hery Djagat Purnomo; Adriyan Pramono; Endang Mahati; Etika R. Noer (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
Cirrhosis is the final stage of all chronic liver diseases. Complications that occur are malnutrition. Administration of Hepatogomax as an enteral formula with adequate nutrients, specifically Branched-Chain Amino Acids (BCAA) and Medium-chain Triglyceride (MCT), can reduce serum ALP, bilirubin, and GG levels. This study aimed to determine the effect of hepatogomax in different doses on serum ALP, bilirubin, and GG levels. The study used the True Experimental post-test group design. Twenty-four male rats were divided into control group K normal and K(-) cirrhotic, treatment groups P1 and P2, given TAA and hepatogomax induction, respectively, at doses of 4,87 g/200gBW/day and 14,6 g/200gBW/day. Intervention for 28 days at the PAU Laboratory, Gadjah Mada University, February 2022 to April 2022. Statistical analysis used the Kruskal Wallis and Mann Whitney Post Hoc tests. The data is the result of examining serum levels after the intervention. The results showed significant differences in ALP, bilirubin, and GGT (p<0,05) in the group of rats induced by TAA intervention with hepatogomax compared to those not given hepatogomax. There was no significant difference in the decrease in serum ALP levels between the K normal (p<0,05) and P2 (p>0,05) groups. Giving hepatogomax at a dose of 14,6 g/200BB/day reduced serum ALP, bilirubin, and GG levels. In conclusion, Hepatogomax decreased ALP, bilirubin, and GGT serum levels in rats with cirrhosis. The most significant decrease in serum ALP, bilirubin, and GGT levels was observed at the P2 dose.